Menggali Potensi Ekonomi Perempuan Desa, Konversi Pekerja Sektor Tradisional Menuju Ekonomi Kreatif Desa Neulop II Kecamatan Indrajaya - Wardiana, Lila; Jayanti, Ery (Yayasan Sagita Akademia Maju, 2025)
The aim of this service is to introduce the creative economic sector to Village Women so that their family's income and quality of life increase, and they are able to change their thinking.The powerlessness of rural women has an impact on the low quality of life, therefore converting the traditional economic sector to the creative economic sector is one solution that must be appreciated.The results of this activity have provided significant changes after the Fesa Neulop II women received training, understanding, and direct practice from the Community Service Team. Housewives and young women have access to creativity, culinary knowledge, and aesthetic presentation in handicrafts, thereby increasing family income and welfare.